DNA testing reveals hidden benefits of improved crop varieties for Ethiopian farmers - Jovanovic, Nina; Ricker-Gilbert, Jacob (International Food Policy Research Institute, 2025)
Increasing farmer adoption of improved crop varieties is a key way to improve agricultural productivity and reduce poverty in low-income countries. Yet in these areas, smallholder farmers’ reported yields for such varieties often fall far short of researchers’ and policymakers’ expectations.